Nicht-analoge französische und italienische Übersetzungen von restriktiven Partikeln im Roman Die Mittagsfrau von Julia Franck - Nicklaus, Martina (Linguistik Online, 2015)
The present paper discusses the translation of German nur and some synonymous restrictive particles into French and Italian in authorized literary translations. Only non-analogous translations of the restrictive particles have been considered, such as It. si limitò a sorridere for Germ. sie lächelte nur (’she limited herself to smiling’ vs. ’she only smiled’). Three types of non-analogous equivalents of nur could be found in the data-base: cleft constructions, verbal periphrases and verb-infinitive combinations. The use of these Italian and French expressions seems to be constantly linked to co-textual features. The description of these non-analogous equivalents contributes to a better delineation of language-specific preferences concerning the encoding of restriction. Furthermore the description leads to helpful suggestions for translations from French/Italian into German, encouraging translators to substitute e.g. a finite, main verb (It. limitarsi) for a simple particle (Germ. nur) in order to get adequate solutions in German.